Relevant knowledge: content analysis of research conducted by South African psychology masters students (2008-2012 - Whitehead, Tracey (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
In South Africa, Psychology has had a chequered past mainly due to its role in the justification of apartheid policies. Due to apartheid's socio-economic injustices, confidence in the applicability of psychological knowledge to South Africa's social problems was insufficient. Psychologists attempted to raise consciousness of the social relevance of psychology by contributing relevant knowledge and being reactive to social inequalities and related psychosocial issues affecting South Africa. This study aimed to conduct a content analysis of trends in research produced by Psychology Masters' students in the fields of Clinical, Counselling and Research psychology over a period of 5 years (2008-2012). The corpus of data was then compared with the key issues raised in the United Nations Development Programme's South Africa human development report (2003), along with a focus on articles published by Macleod (2004) and Macleod and Howell (2013). It emerged that Empirical Qualitative studies, based on post-modern frameworks, as well as HIV/AIDS, Knowledge Production, Assessment and Measurement and Programme development and evaluation, dominated psychological research. Participants were mainly urban, middle class adults living in the 3 wealthiest provinces. University students were the most popular participant group. While it is encouraging that students were attempting to engage with psychosocial issues, the limited number of key social issues addressed, the under-representation of certain sectors of the South African population, as well as the impact of socioeconomic status on well-being requires greater attention at Masters' level to ensure Psychology's psychosocial relevance.
Keywords: Psychology -- Research -- South Africa; Psychology -- Study and teaching (Higher) -- South Africa; Psychology students -- South Africa